2020
DOI: 10.3389/fmicb.2020.01403
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Inoculation of Young Calves With Rumen Microbiota Does Not Significantly Modulate the Rumen Prokaryotic Microbiota Consistently but Decreases Diarrhea

Abstract: The complex rumen microbiota exhibits some degree of host specificity. The undeveloped simple rumen microbiota is hypothetically more amendable. The objective of this study was to investigate if the rumen prokaryotic microbial assemblage of young calves can be reprogrammed by oral inoculation with rumen microbiota of adult cows. Twenty newborn male calves were randomly assigned to four groups (n = 5 per group), with two groups being orally inoculated with rumen microbiota (fresh rumen fluid) collected from two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 85 publications
2
16
0
1
Order By: Relevance
“…Spermidine and putrescine are synthesized from arginine [ 56 ] and possibly related to handling oxidative stress in the rumen [ 57 ]. The transport system of those polyamines was differentially abundant by both the BE and PE treatment and this is in agreement with the result of previous repeated adult rumen fluid treatment study with male calves [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Spermidine and putrescine are synthesized from arginine [ 56 ] and possibly related to handling oxidative stress in the rumen [ 57 ]. The transport system of those polyamines was differentially abundant by both the BE and PE treatment and this is in agreement with the result of previous repeated adult rumen fluid treatment study with male calves [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…Adult-derived rumen microbial inoculation of dairy calves has been studied as a potential probiotic application facilitating the transfer of numerous microbes at once. While adult-rumen microbial inoculation studies with young ruminants didn’t significantly impact rumen microbial populations and animal growth measurements [ 8 , 9 ], potential beneficial effects on gut health, fermentations, and rumen development have been demonstrated [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dairy calves have much simpler rumen microbiota before weaning than that of post-weaning, but its composition has shown rapid changes by the onset of solid feeding (Jami et al, 2013;Rey et al, 2014). Other researchers have administered microbial inocula during a similar feeding period to enable young ruminants to establish a more diverse microbial community (Belanche et al, 2020;Bu et al, 2020;Yu et al, 2020), which is suggested to facilitate the utilization of complex lignocellulosic contents in the rumen (Ribeiro et al, 2017). In our previous study with pre-weaned dairy calves (3-6 weeks of age), we confirmed that repeated rumen fluid inoculation moderately affected ruminal fermentation parameters, bacterial diversity measurements and composition (Cersosimo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea is one of the leading causes of decreased productivity and death in ruminants that has been considered a vital factor impeding animal husbandry development in many countries ( Musso et al, 2011 ; Ambalam et al, 2016 ). Early investigations revealed that diarrhea was present in almost all ruminants and especially epidemic in neonatal goat, sheep, cattle, and yak with immature gastrointestinal tract, which caused approximately half of all ruminant deaths ( Li et al, 2018 ; Bu et al, 2020 ; Xue et al, 2020 ). Previous research has indicated that some intestinal microbes including bacteria and fungi of ruminants alternate between preponderant and weak populations accompanied by diarrheic symptoms ( Yang et al, 2017 ; Wang et al, 2018 ; Wang et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%